Microbiota composition and its impact on DNA methylation in colorectal cancer - Gutierrez-Angulo, Melva; Ayala-Madrigal, Maria de la Luz; Moreno-Ortiz, Jose Miguel; Peregrina-Sandoval, Jorge; Garcia-Ayala, Fernando Daniel (Frontiers in Genetics, 2023)
Colorectal cancer is a complex disease produced by interaction of genetics, epigenetics and environmental factors. DNA methylation is frequently found in tumor suppressor genes to promote the cancer development. Several factors are associated with changes in DNA methylation pattern and recently, the gastrointestinal microbiota could be associated with this epigenetic change. The predominant phyla in gut microbiota are Firmicutes and Bacteroidetes, however, an enrichment of Bacterioides fragilis, Fusobacterium nucleatum, Streptococcus bovis, among others have been reported in colorectal cancer, although the composition could be influences by several factors including diet, age, sex and cancer stage. Fusobaterium nucleatum, a gram-negative anaerobic bacillus, is mainly associated with colorectal cancer patients positive for CpG island methylator phenotype, although hypermethylation in genes as MLH1, CDKN2A, MTSS1, RBM38, PKD1, PTPRT and EYA4 have also been described. Moreover, Hungatella hathewayi, gram-positive rod-shaped bacterium, is related with hypermethylation in SOX11, THBD, SFRP2, GATA5, ESR1, EYA4, CDX2 and APC genes. The epigenetic mechanism is unclear, although they could be implicated in DNA methyltransferases regulation, enzymes that catalyze the transference of methyl group on cytosine of CpG sites. Since DNA methylation is a reversible event, changes on gut microbiota could modulate the gene expression through DNA methylation and improve the colorectal cancer prognosis.